The Linkage Between Marketing Intensity and Firm Performance : A Quantile Regression Approach - Soni, Tarun Kumar; Sirohi, Rajeev; Jamwal, Divya Singh (Indian Journal of Marketing, 2024)
Purpose : This study comprehensively analyzed how marketing intensity affected a firm’s performance across various quantiles of profit distributions for Indian manufacturing firms. Methodology : This study employed a panel quantile regression approach and used a comprehensive dataset comprising financial and marketing performance metrics from a diverse sample of Indian manufacturing sector firms over the past 12 years. This study used several proxies for marketing intensity: the actual expenditure on advertising, promotion, distribution, and pricing. It also controlled for several firm-level controls, including past profitability, leverage, foreign market knowledge, liquidity, and risk. Findings : The performance of domestic manufacturing enterprises was favorably connected with marketing intensity, as demonstrated by the data. The findings additionally indicated that, after sales promotion expenses, distribution expenditures have the largest positive influence on business success. Furthermore, when analyzing the correlation between company profitability and the various proxies of marketing intensity, we found larger differences in performance across the lower, medium, and higher quantiles. Practical Implications : The results of this study provided insights into how the relationship between marketing intensity and firm performance changes across different quantiles and whether the results were significantly different for the four parameters of marketing intensity. The results confirmed that the distribution intensity coefficient was larger than the promotion and advertisement intensity coefficients, suggesting that the distribution investment was more impactful than the other two marketing intensity measures. Originality/Value : This information could aid manufacturing firms in planning their marketing resources and strategies to increase profitability. It could also help decision-makers allocate firm resources more efficiently across different measures of marketing intensity.